Balance Reward and Safety Optimization for Safe Reinforcement Learning: A Perspective of Gradient Manipulation - Gu, Shangding; Qin, Hong Cheng, Hang Dong, Bo Qiao, Si; 林庆维, Qingwei Lin (2024)
To come soon.